EXPERIMENTAL INVESTIGATION OF WATER ENTRY IMPACT ON HYDROPHOBIC SURFACES - Guzel, Bulent; Korkmaz, Fatih C. (AMER SOC MECHANICAL ENGINEERS, 2015)
The results of an experimental investigation on hull bottom slamming of three different geometries, sphere, cylinder and wedge, with hydrophobic surfaces are presented. In water entry of blunt bodies, different fluid dynamics phenomena like jet formation, cavity formation, water splashing, flow separation on solid surfaces and air entrapment between solid and liquid surface have been studied for decades. Our study is aimed at understanding and modeling the dynamics of slamming under an extended range of parameters including hydrophobic surfaces. In this study, drop tests have been set up for hull bottom slamming by dropping a body from various heights toward water surface. From digital images captured using a high speed camera, flow separation and water splashing at different velocities are observed and spreading diameters and entrance characteristics are measured during the impact process. At the same time, we measure the pressure distribution on the surface of the bodies during impact via strain gages.
Keywords: LOADS; Engineering